2021
DOI: 10.3390/app11031300
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Performance of Aluminium Matrix Composites Reinforced with Refractory High-Entropy Alloy Particulates

Abstract: Novel aluminium matrix composites reinforced by MoTaNbVW refractory high-entropy alloy (HEA) particulates have been fabricated by powder metallurgy. The microstructure of the produced composites has been studied and the corrosion behaviour assessed in 3.5% NaCl solution. The composites exhibited low porosity, good homogeneity, few defects, and good distribution of the reinforcing phase in the Al matrix. No secondary intermetallic phases have been formed while the interface between matrix/reinforcement showed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 51 publications
(78 reference statements)
2
11
0
Order By: Relevance
“…In this test, the residual depth is an appropriate criterion for evaluating the wear resistance of the material. This test is frequently used to compare the wear resistance of various materials processed in different conditions [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. The AFM images from longitudinal scratches of the bulk As can be seen, the residual depth of the Fe 3 Al compound is larger than that of the (Fe,Ti) 3 Al sample.…”
Section: Resultsmentioning
confidence: 99%
“…In this test, the residual depth is an appropriate criterion for evaluating the wear resistance of the material. This test is frequently used to compare the wear resistance of various materials processed in different conditions [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. The AFM images from longitudinal scratches of the bulk As can be seen, the residual depth of the Fe 3 Al compound is larger than that of the (Fe,Ti) 3 Al sample.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the functional and mechanical properties of the composites AlCoCrCuFeNi-cBNCoMo and AlCoCrCuFeNi-B4CCoMo, we implemented high-energy machining of powder mixtures in a water-cooled centrifugal ball mill GEFEST-2 (AGO-2U). The ball mill has the following parameters: drum volume-150 cm 3 ; ball acceleration-40 g ball ratio for loading (10)(11)(12)(13)(14)(15):1; ball diameter-6 mm; ball material-WC; carrier speed-890 rpm; and drum speed-1000 rpm. We carried out high-energy machining in an inert environment (argon).…”
Section: High-energy Machiningmentioning
confidence: 99%
“…The experimental data were processed using the Statistica v10.0 application package in the SPSS environment. The analysis of the results obtained shows (Figure 7a) that material Hastelloy X (NiCrFeMo) (I = 46.16 × 10 −6 g/m, disk pressure P = 9.4 MPa) has the highest wear rate (Figure 7a The wear rate (I) from the pressure (P) of the disk changes according to polynomial dependence (Figure 6a) and is described by empirical Equations ( 7)- (10). The equations were obtained from the mathematical analysis of experimental data using Statistica v10.0 software: AlCoCrCuFeNi-B4CCoMo: I = −8.77…”
Section: Performance Properties Of Surface-modified Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [ 14 ] considered the powder metallurgy route to fabricate a copper matrix composite with AlCoNiCrFe as the reinforcement phase and found that the yield strength of composites was enhanced by approximately 160% compared with the yield of the Cu matrix, and the elongation increased by approximately 15%. Ananiadis et al [ 15 ] studied the microstructure and corrosion performance of Al matrix composites reinforced with refractory (MoTaNbVW) HEA particulates. The composite was fabricated through the powder metallurgy route, and it was reported that increasing the volume of the reinforcing phase enhanced the composite’s hardness.…”
Section: Introductionmentioning
confidence: 99%